Tinjauan Pelayanan Publik sebagai Instrumen Perwujudan Good Governance Melalui Pelayanan Administrasi Kependudukan - Endi Sudadi (International Forum of Researchers and Lecturers, 2024)
of Higher Education Dharma. When the functions of instructors and students become an integral part of the activity. It is believed that through participation in PKM (Community Service activities), lecturers, students, and community members will work together in harmony to raise awareness of the unique needs of the community. The goal of the government, both local, sub-district, and village governments, is to ensure that all citizens are treated fairly when applying and receiving population documents through the implementation of the Population Administration Service system. Observation, interviews, and documentation are the main tools to collect information in this qualitative descriptive research method. Population administration services based on the principles of good governance are very important to improve the quality of public services. This is driven by the need for public service providers in population administration services that show good governance, as well as people's aspirations for quality public services in this era of decentralization.